WITH COLOR EXPRESSIONS IN PROVERBS / IDIOMS: लोकोक्ति/मुहावरों में रंग भावों के संग - Srivastava, Sushma (International Journal of Research -GRANTHAALAYAH, 2014)
The proverb is directly related to the expression side of the common people. Experience of the reality of human life is embedded in the background of the proverb. It is related to the eternal truth. The proverb is complete in itself. It freely connotes a specific meaning. The proverb and idiom provide the elixir of language. Using them, the language incorporates liveliness, simplicity, pictorialism and efficacy. The word ’idiom’ derives from the Arabic language which means ’practice’ or ’conversation’ but now this word conveys a special meaning. Idioms are used as sentences in sentences. "A phrase prevalent in written or poetic language, which is proved by the symptom or euphemism due to its singular meaning in general, is called idiom." We can also call it symptomatic language. लोकोक्ति का सीधा संबंध जनसामान्य के अभिव्यक्ति पक्ष से है। लोकोक्ति की पृष्ठभूमि में मानव-जीवन के यथार्थ का अनुभव सन्निहित होता है। यह चिरंतन सत्य से संबंधित होती है। लोकोक्ति अपने आप में पूर्ण होती है। यह स्वतंत्र रूप से विषेष अर्थ को ध्वनित करती है। लोकोक्ति ओर मुहावरे भाषा के उत्कर्ष का विधान करते हैं। इनके प्रयोग से भाषा में सजीवता, सरसता, चित्रात्मकता व प्रभावोत्पादकता का समावेष होता है।‘मुहावरा‘ षब्द अरबी भाषा से निकला है जिसका मूल अर्थ है ‘अभ्यास‘ या ‘बातचीत‘ किन्तु अब इस षब्द से एक विषेष अर्थ ध्वनित होता है। मुहावरों का प्रयोग वाक्य मे ंवाक्यांष के रूप में होता है। ”लिखित अथवा काव्य भाषा में प्रचलित वह वाक्यांष जिसका अर्थ सामान्य अर्थ से विलक्षण होने के कारण लक्षणा अथवा व्यंजना द्वारा सिद्ध होता है उसे मुहावरा कहते हैं।“ हम इसे लक्षणा प्रधान भाषा भी कह सकते हैं।